Peranan Teknik Compressed Sense (CS) pada Pemeriksaan MRI Lumbosacral dengan Kasus Hernia Nucleus Pulposus (HNP) - Safruddin, Muhammad; Diartama, Anak Agung Aris; Triningsih, Triningsih (Poltekkes Kemenkes Semarang, 2025)
Background: The number of Lumbosacral MRI examinations at the Radiology Department of the Regional General Hospital of West Nusa Tenggara Province averages 80 patients per month, with the most common case being Hernia Nucleus Pulposus (HNP). The normal duration for each examination is 17-20 minutes. Compressed Sense (CS) was always activated during the author's observation of these examinations, reducing the total scan time for Lumbosacral MRI examinations to 8 minutes. In some MRI cases, there are challenges with non-cooperative patients, such as traumatic cases and being unable to supine position, which causes moving artifacts and makes image results blur, activating the CS technique can solve this problem making examination times faster. The research aims to analyze and describe the technique, the role of the technique, as well as the advantages and disadvantages of the CS technique in Lumbosacral MRI examinations for HNP cases.Methods: This research is qualitative descriptive research with a case study and literature review approach. use 3 patients, 3 radiographers, dan 3 radiologists, do in March to April 2024. Data was collected by observation, deep interviews, and questionnaires for radiologists about image quality.Result: Three patients with clinical HNP underwent Lumbosacral MRI examinations without any special preparation. The Lumbosacral MRI protocol includes Survey, Coronal T2W TSE, Sagittal T1W TSE, Sagittal T2W TSE, Sagittal T2W TSE SPIR, Axial T1W TSE, Axial T2W TSE, and MYELO Radial. The protocols use the CS technique with a reduction score of 1.4, except MYEOLO Radial, which can reduce scan time to 7-10 minutes without decreasing image quality. The sequences used serve to provide anatomical information and pathology in the lumbosacral area.Conclusions: Lumbosacral MRI examinations using the Compressed Sense technique can shorten the examination time without significantly reducing the quality of the images produced, it proved by the questionnaire result. This can increase patient comfort during the examination. The use of reduction values in this CS technique must be considered as it can increase the value of Peripheral Nerve Stimulation (PNS).